Sustained release of a GLP-1 and FGF21 dual agonist from an injectable depot protects mice from obesity and hyperglycemia - Gilroy, C. A. (Sci Adv, 2020)
There is great interest in identifying a glucagon-like peptide-1 (GLP-1)–based combination therapy that will more effectively promote weight loss in patients with type 2 diabetes. Fibroblast growth factor 21 (FGF21) is a compelling yet previously unexplored drug candidate to combine with GLP-1 due to its thermogenic and insulin-sensitizing effects. Here, we describe the development of a biologic that fuses GLP-1 to FGF21 with an elastin-like polypeptide linker that acts as a sustained release module with zero-order drug release. We show that once-weekly dual-agonist treatment of diabetic mice results in potent weight-reducing effects and enhanced glycemic control that are not observed with either agonist alone. Furthermore, the dual-agonist formulation has superior efficacy compared to a GLP-1/FGF21 mixture, demonstrating the utility of combining two structurally distinct peptides into one multifunctional molecule. We anticipate that these results will spur further investigation into GLP-1/FGF21 multiagonism for the treatment of metabolic disease.